Validation and application of auxiliary density perturbation theory and non-iterative approximation to coupled-perturbed Kohn-Sham approach for calculation of dipole-quadrupole polarizability - Shedge, Sapana V.; Pal, Sourav; Koester, Andreas M. (Chemical Physics Letters, 2011)
Recently, two non-iterative approaches have been proposed to calculate response properties within density functional theory (DFT). These approaches are auxiliary density perturbation theory (ADPT) and the non-iterative approach to the coupled-perturbed Kohn-Sham (NIA-CPKS) method. Though both methods are non-iterative, they use different techniques to obtain the perturbed Kohn-Sham matrix. In this Letter, for the first time, both of these two independent methods have been used for the calculation of dipole-quadrupole polarizabilities. To validate these methods, three tetrahedral molecules viz., P-4; CH4 and adamantane (C10H16) have been used as examples. The comparison with MP2 and CCSD proves the reliability of the methodology. (C) 2011 Elsevier B. V. All rights reserved.

Vibrational multi-reference coupled cluster theory in bosonic representation - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2012)
The vibrational multi-reference coupled cluster method is developed to calculate the vibrational excitation energies of polyatomic molecules. The method is implemented on ozone and formaldehyde molecules and the results are compared with full vibrational configuration interaction (FVCI) method. A good agreement is found between the vibrational multi-reference coupled cluster method and converged FVCI method for lower lying vibrational states. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4753422]